(untitled) (International Journal of Engineering and Computer Science, 2016)
This paper presents a whole new concept or approach for Green Computing or Environment friendly computing. Model of cloud computing has enabled convenient and ubiquitous network access to a shared pool of configurable computing resources that can be quickly provisioned and released with minimal interaction with the service providers. In this paper we have developed an algorithm which will migrate virtual machines in data centres in accordance to the availability of non-conventional and renewable sources of energy i.e. wind energy, hydro power, solar power, geothermal power & etc. The proposed migration algorithm is general in nature but goes beyond conventional approach of best fit heuristic. Experimental verification shows the ability of the VMs to migrate it in accordance to the availability of different sources of renewable energy.